Seeds of change: cultivating feminist leadership in the co-operatives of the MENA region - Najjar, Dina; Oueslati, Dorsaf; Ben Ghanem, Hajer; El Amil, Rola; Ait Hssain, Jihad; Nidkazza, Zakaria; Benrais, Brahim; Kallida, Rajae; Oussoulous, Nada (Taylor and Francis Group, 2025)
This paper examines women’s leadership in local group governance in Morocco, Tunisia, and Lebanon, highlighting rural co-operatives as key spaces for socioeconomic participation and agency. Based on interviews and focus groups with a total of 917 participants (688 women and 170 men co-operative members, and 59 officials), the study identifies major barriers to women’s leadership, including financial limitations, lack of training, gender stereotypes, and exclusion from policy processes. Despite these obstacles, women-led co-operatives foster economic independence, collective agency, and more-inclusive governance. However, their impact is constrained by normative and policy environments where gender-sensitive governance remains weak. Using Morocco as a case study, the research evaluates targeted interventions – capacity strengthening, theatre forum, and governance workshops – that have enhanced women’s leadership and shifted local perceptions. The study calls for multi-level reforms to expand access to resources and training, challenge restrictive norms, and strengthen co-operation between co-operatives, authorities, and international actors. Empowering women’s grassroots leadership can catalyse broader sociopolitical transformation and advance gender equality across the Middle East and North Africa (MENA) region.